Schaum's outline of theory and problems of introduction to mathematical economics - Dowling, Edward T. (New York : McGraw-Hill, 2001)
Mathematics and Statistics
2003-04-10
Keywords: Mathematics; Economics-Mathematical; Calculas; Linear algebra; Matrix; Differential equations